LukS-PV Induces Apoptosis via the SET8-H4K20me1-PIK3CB Axis in Human Acute Myeloid Leukemia Cells - Xu, Liang Fei; Shi, Lan; Zhang, Shan Shan; Ding, Peng Sheng; Ma, Fan; Song, Kai Di; Qiang, Ping; Chang, Wen Jiao; Dai, Yuan Yuan; Mei, Yi De; Ma, Xiao Ling (Frontiers in Oncology, 2021)
Evidence suggests that histone modification disorder is involved in leukemia pathogenesis. We previously reported that LukS-PV, a component of Panton-Valentine leucocidin (PVL), exerts anti-leukemia activity in AML cells through kinds of mechanisms. Furthermore, LukS-PV inhibits hepatoma progression by downregulating HDAC2, indicating that LukS-PV might regulate histone modification. However, whether LukS-PV exerts anti-leukemia activity by targeting histone modification regulators remains poorly understood. In this study, our results showed that LukS-PV induces cell apoptosis and inhibits cell invasion via flow cytometry. Moreover, we confirmed that SET8 is a potential histone modification targets upon LukS-PV treatment. LukS-PV attenuated SET8 expression and induced apoptosis via downregulating SET8/H4K20me1. Furthermore, ChIP-seq and ChIP-PCR identified that PIK3CB is the target gene for cell apoptosis mediated by SET8/H4K20me1. Finally, our results indicated that LukS-PV induces apoptosis via the PIK3CB-AKT-FOXO1 signal pathway by targeting SET8. The study indicates that LukS-PV induces apoptosis in AML cells by downregulating SET8 and regulating its downstream molecular targets, suggesting that SET8 may be a potential therapeutic target for AML and LukS-PV is a targeted epigenetic drug candidate for the treatment of AML.